(untitled) (Research, Society and Development, 2020)
The fast and accurate detection of patients infected with COVID-19 is extremely important to obtain control in the population and in hospitals. To review recent literature, presenting human saliva as a biofluid for the detection and diagnosis of COVID-19. A bibliographic search was performed in the PubMed (National Library of Medicine) and Scopus Preview databases through CAPES, with the keywords COVID-19 and dentistry, COVID-19 and saliva, from January 2020 to 11 June 2020. Saliva has been widely used to diagnose various diseases, due to its easy access. Thus, saliva has been presented as one of the viable alternatives for the detection of the new coronavirus, since oral spillage is more significant than viremia. The SARS-CoV-2 virus can be found in human saliva, as well as in the salivary gland, presenting itself as a biofluid to test and diagnose COVID-19 disease.